2021
DOI: 10.1007/s00426-021-01528-z
|View full text |Cite
|
Sign up to set email alerts
|

In Colore Veritas? Color effects on the speed and accuracy of true/false responses

Abstract: In addition to their perceptual or aesthetic function, colors often carry conceptual meaning. In quizzes, for instance, true and false answers are typically marked in green and red. In three experiments, we used a Stroop task to investigate automatic green-true associations and red-false associations, respectively. In Experiments 1 and 2, stimuli were true statements (e.g., “tables are furniture”) and false statements (e.g., “bananas are buildings”) that were displayed in different combination of green, red, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 38 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…The finding that the green-yellow IAT did not display an effect in the hypothesized direction might suggest that the association between green and true is weaker than that one between red and false. Yet, Nadarevic et al (2021) observed symmetrical color-validity associations for red and green in the context of each other, and no validity associations for either color when paired with gray. Note, however, that in contrast to the Stroop task used by Nadarevic and colleagues, the IAT indicates relative associations (e.g., the relative strength of green-true vs. yellow-true and green-false vs. yellow-false associations, respectively).…”
mentioning
confidence: 79%
See 4 more Smart Citations
“…The finding that the green-yellow IAT did not display an effect in the hypothesized direction might suggest that the association between green and true is weaker than that one between red and false. Yet, Nadarevic et al (2021) observed symmetrical color-validity associations for red and green in the context of each other, and no validity associations for either color when paired with gray. Note, however, that in contrast to the Stroop task used by Nadarevic and colleagues, the IAT indicates relative associations (e.g., the relative strength of green-true vs. yellow-true and green-false vs. yellow-false associations, respectively).…”
mentioning
confidence: 79%
“…In Experiment 2, gray served as the control color because it appears to be neutral in the context of color-validity associations (Nadarevic et al, 2021). In addition, we used easy mathematical equations instead of statements as stimuli for the categories true and false to see if the effects would replicate with these materials.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations